Attitudes towards people with disabilities: a systematic Rreview of intervention effectiveness - Castillo, Yuleinys A; Larson, Alan (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
The improvement of attitudes towards people with disabilities has led to studies focusing on the impact of interventions. This review systematically analyzes and synthesizes the use of interventions to influence attitudes toward people with disabilities. A comprehensive search was conducted across multiple databases to identify studies that used an intervention in English with a defined assessment instrument meant to measure attitudinal changes toward people with disabilities. Based on a literature research, 32 studies conducted in fourteen different countries were included. In the majority of the cases, the use of interventions was an effective tool to improve attitudes towards disabilities. Implications of findings for practitioners and researchers are discussed.